In vitro evaluation of the effects of graphene platelets on glioblastoma multiforme cells - Jaworski S (Dove Medical Press, 2013)
Slawomir Jaworski,1 Ewa Sawosz,1 Marta Grodzik,1 Anna Winnicka,2 Marta Prasek,1 Mateusz Wierzbicki,1 André Chwalibog31Division of Biotechnology and Biochemistry of Nutrition, Faculty of Animal Science, 2Department of Pathology and Veterinary Diagnostics, Faculty of Veterinary Medicine, Warsaw University of Life Sciences, Warsaw, Poland; 3Department of Veterinary Clinical and Animal Sciences, University of Copenhagen, Copenhagen, DenmarkAbstract: Graphene is a single atom-thick material with exciting potential. It can be used in many fields, from electronics to biomedicine. However, little is known about its toxicity and biocompatibility. Herein, we report a study on the toxicity of graphene platelets (GPs) by examining the influence of GPs on the morphology, mortality, viability, membrane integrity, and type of cell death of U87 and U118 glioma cells. It was found that graphene is toxic to glioma cells, but it activated apoptosis only in the U118 cell line, without inducing necrosis, indicating the potential applicability of GP in anticancer therapy.Keywords: toxicity, glioma, apoptosis